2015
DOI: 10.1021/acs.jpcc.5b01137
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from Red to Blue Photoluminescence in Alcohol Dispersions of Alkyl-Capped Silicon Nanoparticles: Insight into the Origins of Visible Photoluminescence in Colloidal Nanocrystalline Silicon

Abstract: Visibly emissive silicon nanoparticles (Si NPs) were obtained via annealing of (HSiO 1.5 ) n polymer, followed by chemical etching. The hydrideterminated Si NPs (H-Si NPs) were surface-functionalized via thermal hydrosilylation with 1-decene and were dispersed in straight chain alcohols varying in carbon chain length (C1−C10). The initial red photoluminescence (PL) (λ max,em ∼580 nm) observed from hexane dispersions of the decane-terminated Si NPs (dec-Si NPs) became weaker upon exposure to alcohols smaller th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…Some authors claim that this PL is unrelated to Si NCs, attributing it residual chlorine‐based impurities . It was also connected with to the presence of nitrogen, whereas some claim it to be the result of oxidation of Si NCs:C . To make the situation even more complicated, in some SiNCs (prepared without chlorine or nitrogen) the fast PL was attributed to the core‐related states .…”
Section: Luminescencementioning
confidence: 99%
“…Some authors claim that this PL is unrelated to Si NCs, attributing it residual chlorine‐based impurities . It was also connected with to the presence of nitrogen, whereas some claim it to be the result of oxidation of Si NCs:C . To make the situation even more complicated, in some SiNCs (prepared without chlorine or nitrogen) the fast PL was attributed to the core‐related states .…”
Section: Luminescencementioning
confidence: 99%
“…68 For this reason, the red emission (related to quantum connement) progressively decreases in intensity and slightly shis to shorter wavelength (from about 635 nm to about 600 nm aer 90 days). Conversely, the optical emission at 400 nm (blue band) has signicantly more emission thus suggesting that it might be attributed to the surface defects at the nanocrystallites induced by nitrogen containing compounds ascribed to the amino groups, 69 which are progressively released because of the dissolution of chitosan and interaction with pSi. 70,71 According to the above results, we were able to stabilize the PL intensity and feature it up to months in a high ionic strength aqueous buffer such as PBS.…”
Section: Emission Stability In Biological Mediamentioning
confidence: 99%
“…The observation of good emission properties from biocompatible SiNPs have attracted the interest of scientists for studying applicability of these materials in biomedical field such as fluorescence imaging labels [22,23], bio-functional probes [24,25], bioimaging contrast agents and therapy [26][27][28]. Although the optical properties of silicon nanostructure have been mainly ascribed to the quantum confinement size effect, control of surface characteristics is one of the most challenging aspects that have important effects on the visible to near-infrared photoluminescence (PL) emissions of the SiNPs [29][30][31][32][33][34][35][36][37][38]. It was shown that PLA of silicon in liquid media is a simple one-step technique, suitable for producing SiNPs with subsequent surface modifications.…”
Section: Introductionmentioning
confidence: 99%